Surface marker-assisted for orbital navigation surgery: a dry skull study - Nazimi Abd Jabar,; Nuraudi Zafirah AR,; Nur Syaira I,; Izhar AA,; Muhd Fazlynizam R, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
The purpose of this study was to explore a surface marker-assisted method for orbital floor reconstruction. Six adults, dry human skulls were used in this study. First, an individualised, 0.4 mm aluminum orbital implant was prepared for orbital floor bilaterally. Four physical implant surface markers in the anterior and posterior aspects of the implant were created and subjected for an optical scan. Preoperative cone beam computed tomography (CBCT) scans were obtained for all orbital floors. The Digital Imaging and Communications in Medicine (DICOM) data were retrieved, imported and virtually reconstructed with its respective orbital implant stereolithography (STL) data by using iPlan CMF (Version 3.0, BrainLab, Germany). Navigation image-fusion technique was performed for each skull following navigation-assisted reconstruction and postoperative CBCT. Computed tomography (CT)-assisted measurements of the implant positions were evaluated between the virtually planned and realized implant positions in its translational differences sagittal and coronal planes. All statistical analysis was performed using PASW® Statistics Version 18. Results showed that38 out of the 48 surface markers evaluated showed a small elevation in realized compared to the virtual orbital implant position. Translation for the Euclidean metric showed differences of less than 1.00 mm in all surface markers except at the posterior ledge and anterior when assessed in the sagittal plane. The study showed that the placement of surface marker-assisted in orbital navigation surgery provides a consistent orbital implant position.